A classified and comparative review of Poly(2, 5-dithienyl-N-substituted-pyrrole) derivatives for electrochromic applications. (15th July 2022) - Bezgin Carbas, Buket; Ergun, Emine Gül Cansu
Graphical abstract: Abstract: Poly(2, 5-dithienyl-1-substituted-pyrrole) derivatives are one of the important classes for conducting polymers, exhibiting versatile electrochromic property besides used material in a broad range of smart applications. This review offers an overview of various SNS derivatives, mostly for electrochromic applications. In this compilation, the designed, synthesized and electrochemically and optically characterized conducting polymers of SNS derivatives in the literature up to today have been classified and comparatively discussed. The polymers of the SNS derivatives collected here have been prepared mostly by electrochemical techniques. According to N-substitutions form pyrrole unit, P(SNS) derivatives were grouped into five sections: N- alkyl-, phenyl-, amine/amide-, homo/heterocyclic-, and crosslinked substituted derivatives. Each section mainly includes the structure–property relationship and the comparison of the effect of substitutions on the electrochromic properties of the resulting polymers.